Socially-engaged Scholarship: A Systemic Approach and Academic Benefits - Mingchai, Chedsada (Area Based Development Research Journal, 2021)
The central objective of this article is to discuss 1) a link between thinking and working approaches to socially-engaged scholarship in higher education institutions; and 2) the collective process of producing a socially-engaged academic work for an academic title application. Socially-engaged scholarship is an academic service delivered by universities under the framework of Scholarship of Application through participatory approaches. The academic service should be scholarly designed based on the needs of the society for solution or betterment, with the aim to achieve two concurrent changes: social and academic contributions. Apart from the goals of providing solutions and creating a body of knowledge, a socially-engaged work can be academically exploited in publication for tenure at the assistant professor, associate professor, professor levels. The publication shall be structured in seven sections as prescribed in the criteria. However, the utmost significance of socially-engaged scholarship is preferably placed on providing learning opportunities and establishing mutual learning spaces between the university and the community in solving problems and promoting multifaceted developments as well as empowering university instructors to be ‘practicing scholars’ and community residents to be ‘scholarly practitioners’.